2021
DOI: 10.1007/s00441-020-03390-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences of autism candidate genes on circuit wiring and olfactory decoding

Abstract: Olfaction supports a multitude of behaviors vital for social communication and interactions between conspecifics. Intact sensory processing is contingent upon proper circuit wiring. Disturbances in genetic factors controlling circuit assembly and synaptic wiring can lead to neurodevelopmental disorders, such as autism spectrum disorder (ASD), where impaired social interactions and communication are core symptoms. The variability in behavioral phenotype expression is also contingent upon the role environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 173 publications
2
1
0
Order By: Relevance
“…Individuals with a high dSSP score, that is, those with an excess of hyper-sensory processing sensitivities, displayed a significant trend for the enrichment of deleterious gene mutations in the GABAergic pathway. Our results were in accordance with numerous reports describing the association between genes affecting directly (such as GABRA4, GRIN1) or indirectly (such CACNA1C, SHANK1-3, CNTN3-6) the GABAergic pathway homeostasis and sensory processing divergences in autism spectrum (Hartig et al, 2021;Leblond et al, 2014;Mercati et al, 2017;Tavassoli et al, 2021). The excess load of deleterious mutations affecting the genes of GABAergic pathway reported in our study may reduce the GABAergic tone (Ferguson & Gao, 2018)-as previously showed (Sapey-Triomphe et al, 2019)-and may explain the hypersensitivity observed in autism spectrum.…”
Section: Discussionsupporting
confidence: 93%
“…Individuals with a high dSSP score, that is, those with an excess of hyper-sensory processing sensitivities, displayed a significant trend for the enrichment of deleterious gene mutations in the GABAergic pathway. Our results were in accordance with numerous reports describing the association between genes affecting directly (such as GABRA4, GRIN1) or indirectly (such CACNA1C, SHANK1-3, CNTN3-6) the GABAergic pathway homeostasis and sensory processing divergences in autism spectrum (Hartig et al, 2021;Leblond et al, 2014;Mercati et al, 2017;Tavassoli et al, 2021). The excess load of deleterious mutations affecting the genes of GABAergic pathway reported in our study may reduce the GABAergic tone (Ferguson & Gao, 2018)-as previously showed (Sapey-Triomphe et al, 2019)-and may explain the hypersensitivity observed in autism spectrum.…”
Section: Discussionsupporting
confidence: 93%
“…We speci cally observed mutations affecting the genes as GABARAPL1, GABBR2,…(Supplementary Table 2). Our results were in accordance with numerous reports describing the association between genes affecting directly (such as GABRA4, GRIN1) or indirectly (such CACNA1C, SHANK1-3, CNTN3-6) the GABAergic pathway homeostasis and sensory processing atypicalities in ASD (Leblond et al, 2014;Mercati et al, 2017;Tavassoli et al, 2021, Hartig et al, 2021. The excess load of deleterious mutations affecting the genes of GABAergic pathway reported in our study may reduce the GABAergic tone (Ferguson and Gao, 2018) -as previously showed (Sapey-Triomphe et al, 2019) -and may explained the hypersensitivity observed in ASD.…”
Section: Discussionsupporting
confidence: 93%
“…The causes and consequences of a disruption of the human sense of smell and currently available treatments of olfactory dysfunction are reviewed by Schäfer et al (2021). The last review of this series deals with genetic influence of autism candidate genes on circuit wiring and olfactory decoding (Hartig et al 2021). This review in detail examines the relationship between social odor processing in humans and rodents in the context of health and autism spectrum disorder.…”
mentioning
confidence: 99%